2012
DOI: 10.1007/s00268-012-1729-3
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Surgery and Anesthesia Infrastructure in Ethiopia

Abstract: This survey of Ethiopia's hospital resources attempts to identify specific areas of need where resources, education, and development can be targeted. Because the major surgical mortality comes from late presentations, increasing accessibility through infrastructure development would likely provide a major improvement in surgical morbidity and mortality rates. Infrastructure limitations of electricity, water, oxygen, and blood banking do not prove to be significant barriers to surgical care. The increasing numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 19 publications
5
91
2
Order By: Relevance
“…Generally concurred with findings from previous study, however, found higher reported access to water and electricity, and noted larger variability between urban and rural areas [1,13]. Such resource limitations amplify the burden presented by acute surgical conditions, as found in the capacity assessment performed in Ethiopia [13].…”
Section: Capacity Assessment Coveragesupporting
confidence: 92%
“…Generally concurred with findings from previous study, however, found higher reported access to water and electricity, and noted larger variability between urban and rural areas [1,13]. Such resource limitations amplify the burden presented by acute surgical conditions, as found in the capacity assessment performed in Ethiopia [13].…”
Section: Capacity Assessment Coveragesupporting
confidence: 92%
“…Trauma accounted for most of the orthopedic and half of neurosurgical operations. 1,14,16,[19][20][21] Emergency procedures provide important training for working at district and referral hospitals. Eventually, many of these emergency procedures could be performed at the district level, allowing the referral hospitals to focus on more specialized elective care.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30][31][32][33] However, much of this work was conducted independently and is not well documented, leaving the larger surgical community unaware of prior work, fundraising efforts, and actual effect. To develop a cohesive and effective academic GSI, the first step was to inventory the collective experiences and gauge the interest level of the department's faculty, fellows, and residents.…”
Section: Taking Stock: a Departmental Surveymentioning
confidence: 99%